Dynamic Covalent Bonds in Polymeric Materials. (23rd April 2019) - Chakma, Progyateg; Konkolewicz, Dominik
Abstract: Dynamic covalent bonds (DCBs) have received significant attention over the past decade. These are covalent bonds that are capable of exchanging or switching between several molecules. Particular focus has recently been on utilizing these DCBs in polymeric materials. Introduction of DCBs into a polymer material provides it with powerful properties including self‐healing, shape‐memory properties, increased toughness, and ability to relax stresses as well as to change from one macromolecular architecture to another. This Minireview summarizes commonly used powerful DCBs formed by simple, often "click" reactions, and highlights the powerful materials that can result. Challenges and potential future developments are also discussed. Abstract : Polymere Materialien mit dynamischen kovalenten Bindungen können Eigenschaften wie Selbstheilung und verbesserte Verformbarkeit sowie Spannungsrelaxation und Formgedächtnis aufweisen. Diese Materialien, ihre faszinierenden Eigenschaften und Einsatzmöglichkeiten werden in diesem Kurzaufsatz beschrieben.